Tetracycline marks visible in Baltic cod Gadus morhua otoliths stored for 40 years - Krumme, U.; Bingel, F. (Journal of Fish Biology, 2016)
Baltic cod Gadus morhua otoliths marked with oxytetracycline (OTC) in 1974-1975 had been sectioned and the sections stored in paper envelopes at room temperature in dry, dark conditions. After 40 years of storage, the historic OTC marks were still clearly visible showing that OTC is suitable for long-term chemical marking of otoliths. They were, however, noticeably paler than marks in recently recaptured and archived Baltic G. morhua otoliths, chemically tagged with tetracycline at similar dosage to the historic otoliths. (C) 2016 The Fisheries Society of the British Isles